Olive leaf spot caused by Venturia oleaginea: An updated review - Buonaurio, Roberto; Almadi, Leen; Famiani, Franco; Moretti, Chiaraluce; Agosteo, Giovanni Enrico; Schena, Leonardo (Frontiers in Plant Science, 2023)
Olive leaf spot (OLS) caused by Venturia oleaginea is widespread in all olive-growing areas and continents, where can cause severe yield losses. The disease is often underestimated for the difficulty to reveal early leaf symptoms and for the pathogen-induced phylloptosis, which creates the illusion of healthy and restored plants. The present review provide updated information on taxonomy, pathogen life style and cycle, epidemiology, diagnosis, and control. Application of copper-based fungicides is the main method to control OLS. However, the regulation 2009/1107 of the European Commission include these fungicides in the list of substances candidates for substitution. It is therefore urgent to find alternative control strategies especially for organic agriculture. Among new approaches/strategies for controlling OLS, promising results have been obtained using nanotechnology, endophytic microbes, and biostimulants.